Stunting Prevention Education for Adolescents at Al Falak High School, Bogor City - Sofihidayati, Trirakhma; Rustiani, Erni; Wardatun, Sri (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2023)
Stunting is a condition where growth disorders occur in children which is characterized by a child's lack of height compared to children his age. Several factors cause stunting, especially in the city of Bogor, including lack of nutritional intake in the first 1000 days of life (HPK), early marriage (39 percent), teenagers suffering from anemia (3.52 percent), pregnant women with anemia (11.8 percent ), and the Covid-19 pandemic factor that occurred during the last two years. Anemia in adolescent girls (rheumatism) has an impact on health and performance at school and can be at risk of anemia when they become pregnant mothers, causing suboptimal growth and development of the fetus, potentially causing complications in pregnancy and childbirth, as well as maternal and child death. The Blood Supplement Tablet (TTD) supplementation program for young women started in 2014 and is one of the efforts to reduce stunting. Stunting has an impact on children's growth and development both physically and cognitively, including affecting the growth and development of toddlers, less than optimal motor skills in children, and affecting learning abilities, thus affecting children's IQ. The intervention activities of the UNPAK Community Service (PKM) team on the problem of stunting were carried out on students in grades 11 and 12 of Al Falak High School, Bogor City by providing education about preventing stunting through nutritious food, anemia, blood supplements tablets (BST) containing iron (Fe)) and distribute health information media regarding stunting. It is hoped that this PKM activity will be able to increase knowledge and awareness of teenagers and expectant mothers regarding stunting.